Health in industry - Mackenzie, James; Haldane, William S.
1927-02-25 1927 1920s 4 pages Medical Profession’s Help. Sir John R. Findlay, in moving the adoption of the annual report and financial statement, referred to a habit people have in illness of waiting till the mischief was done before calling in the doctor. The doctors were willing to advise us in the right direction, and one of the achievements of that Society was, he thought, the extent to which it had enlisted the ready and willing and gratuitous services of the medical profession in its great endeavour. (Applause.) Mr. Webster, in seconding, said that during his connection with public life he had found that in no subject had greater advances taken place than in public health. He assured them of the support of his organisation. (Applause.) Dr. Clark Trotter, reporting on work in the various areas, said as an area secretary he had been impressed that the Society’s work supplied quite a long-felt want. Lord Salvesen said he wished to emphasise that the objects for which the Society had been instituted were non-controversial, and that it was non-political. They had secured the support of the Trade Union Congress, and they had necessarily, he thought, the Goodwill of the Employers, because while it was of importance for the operative that he should maintain his health, it was also important for employers that their workmen should not be too often absent through unnecessary causes. The various reports were unanimously adopted. Sir Thomas Oliver, in the course of an address, said that while there were still too many accidents in the field of labour and too large a number of workers made ill through causes connected with' their employment, conditions of labour and the hours of work had become changed in the direction of betterment of the working classes. Votes of thanks to the speakers, to the doctors for their services, to the Dental Board for assistance, to the honorary officials, and to the Chairman were accorded on the motion of Councillor Crawford. WM. S. HALDANE, Chairman. J. MACKENZIE, Gen. Secy. 89 Millbrae Road, Langside, Glasgow, Feb. 25, 1927. 292/840/1/8